Peran Teknologi Informasi dan Komunikasi dalam Meningkatkan Pembelajaran Bahasa Arab: Tinjauan Sistematis Literatur Era Digital - Yasin, Agus (Universitas Islam Negeri Imam bonjol Padang, 2024)
The rapid development of information and communication technology (ICT) has significantly impacted various aspects of life, including education. Integrating ICT into Arabic language learning in the digital era has become increasingly important to enhance the effectiveness and efficiency of teaching and learning processes. This study aims to explore and evaluate the use of ICT in Arabic language learning and to identify the most effective technologies in improving students' language proficiency and learning motivation. This research employs a systematic literature review method, collecting and analyzing data from various previous studies related to the application of ICT in Arabic language education. The findings indicate that the use of mobile-based learning applications, e-learning platforms, and social media positively impacts students' Arabic language skills, increases engagement and motivation, and facilitates broader access to learning materials. However, challenges such as limited technological infrastructure, lack of teacher competency in using ICT, and cultural barriers in technology adoption were also identified. Based on these findings, it is recommended to enhance teacher training, develop better infrastructure, and adapt technology to local cultural contexts. This study provides valuable insights into optimizing ICT for Arabic language learning and offers practical guidelines for developing more effective educational strategies.